Gender and the Work-Family Experience : An Intersection of Two Domains - Mills, Maura J. (Springer International Publishing : Imprint: Springer, 2015)
Conflict between work and family has been a topic of discussion since the beginning of the women's movement, but recent changes in family structures and workforce demographics have made it clear that the issues impact both women and men. While employers and policymakers struggle to navigate this new terrain, critics charge that the research sector, too, has been slow to respond.  Gender and the Work-Family Experience puts multiple faces - male as well as female - on complex realities with interdisciplinary and cross-cultural awareness and research-based insight. Besides reviewing the state of gender roles as they affect home and career, this in-depth reference examines and compares how women and men experience work-family conflict and its consequences for relationships at home as well as outcomes on the job. Topics as wide-ranging as gendered occupations, gender and shiftwork, heteronormative assumptions, the myth of the ideal worker, and gendered aspects of work-family guilt reflect significant changes in society and reveal important implications for both research and policy. Also included in the coverage:  Gender ideology and work-family plans of the next generation Gender, poverty, and the work-family interface The double jeopardy effect: the importance of gender and race in work-family research When work intrudes upon employees' personal time: does gender matter? Work-family equality: the importance of a level playing field at home Women in STEM: family-related challenges and initiatives Family-friendly organizational policies, practices, and benefits through the gender lens Geared toward work-family and gender researchers as well as students and educators in a variety of fields, Gender and the Work-Family Experience will find interested readers in the fields of industrial and organizational psychology, business management, social psychology, sociology, gender studies, women's studies, and public policy, among others.